The Gospel of the King : a commentary on Matthew - Custer, Stewart, 1931- (Greenville, S.C. : BJU Press, 2005)
"This is a devotional commentary on the book of Matthew"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Bible. -- Devotional literature